Discussion: A novel formula for the prediction of swelling pressure of compacted expansive soils - O'Kelly, Brendan (My University, 2020)
Recently, Elsaidy et al. (2019) have proposed a novel empirical model–that is, equation (6) in the original manuscript–for the prediction of the one-dimensional swelling pressure of compacted expansive soils. A total of four expansive soils, designated as soils A, B, C and D in the original manuscript, were examined. According to Table 1 of the original manuscript, the four soils have different degrees of expansivity, ranging from non-expansive to highly expansive. Model development and its calibration were performed using soils A and B, while model validation involved the use of soils C and D, and two additional expansive soils (or datasets) compiled from the literature (i.e.BAS and E&G, as outlined in Appendix B of the original manuscript). The proposed model makes use of the free swell index (FSI) and initial compaction/moulding state parameters of the soil, namely initial water content and dry density. The study under discussion is a welcome addition to the existing literature.Towards addressing some potential issues associated with the investigation of Elsaidy et al. (2019), the discussers would like to elaborate on reported shortcomings associated with the FSI parameter, its correlation with the liquid limit (LL),and the authors’ assumed linear relationships between the FSI and the fitting parameters (αandβ) of their proposed model (i.e. equations (5a) and (5b) in the original manuscript).
PUBLISHED
Keywords: Smart & Sustainable Planet; COMPACTION; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; SOIL PROPERTIES; SOIL STRUCTURE; SOIL WATER; SWELLING; Soil Mechanics; Soil Mechanics & Foundations; expansive clay; geotechnical